2011
DOI: 10.1007/s10709-011-9580-2
|View full text |Cite
|
Sign up to set email alerts
|

New approaches to Prunus transcriptome analysis

Abstract: The recent sequencing of the complete genome of the peach offers new opportunities for further transcriptomic studies in Prunus species in the called post-genomics era. First works on transcriptome analysis in Prunus species started in the early 2000s with the development of ESTs (expressed sequence tags) and the analysis of several candidate genes. Later, new strategies of massive analysis (high throughput) of transcriptomes have been applied, producing larger amounts of data in terms of expression of a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 148 publications
(180 reference statements)
1
19
0
Order By: Relevance
“…Separate microarray analyses of peach and apricot fruits used to profile transcriptome changes during fruit development revealed that 70% of genes had the same expression pattern in both species, but also demonstrated the presence of species-specific transcript changes (Manganaris et al, 2011). Because a high degree of sequence conservation exists within Prunus, the availability of the complete peach genome facilitates the investigation of other members of the genus (Martínez-Gómez et al, 2011). Synteny analysis across species provides insights into the evolutionary interrelationships of different lineages and the opportunity to study the relationship between genome structure and function of organisms (Jung et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate microarray analyses of peach and apricot fruits used to profile transcriptome changes during fruit development revealed that 70% of genes had the same expression pattern in both species, but also demonstrated the presence of species-specific transcript changes (Manganaris et al, 2011). Because a high degree of sequence conservation exists within Prunus, the availability of the complete peach genome facilitates the investigation of other members of the genus (Martínez-Gómez et al, 2011). Synteny analysis across species provides insights into the evolutionary interrelationships of different lineages and the opportunity to study the relationship between genome structure and function of organisms (Jung et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Apricot and peach are diploid species, with apricot possessing a genome slightly larger than that of peach (Geuna et al, 2005). The construction of two apricot linkage maps using simple sequence repeat (SSR) markers has revealed that peach and apricot genomes exhibit complete co-linearity, while sequencing of the complete peach genome has provided opportunities for further studies of other Prunus species (Martínez-Gómez et al, 2011;Verde et al, 2013). The origin of the apricot is disputed.…”
Section: Introductionmentioning
confidence: 99%
“…The DGE profiles produced a large dataset, much greater than with an EST library or microarray Martinez-Gomez et al 2011). By mapping to the peach reference genome v1, a large number of genes were annotated with GO terms and the KEGG pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A major drawback of the cDNA microarray approach for the study of this Gordian knot is that transcriptome profiling coverage is strictly limited to the probe sets available for specific hybridization in each species as we have described before. This classical microarray usually contained EST (cDNA from mRNA) previously developed by Sanger DNA sequencing technology (Aharoni and Vost, 2001;Martínez-Gó mez et al, 2011;Wullscheleger and Difacio, 2003). For this reason, and thanks to the availability of a full genome sequence for some species, new tilling microarray platforms have been developed using different spaced oligonucleotides that span the entire genome of an organism (Comai et al, 2004;Yazaki et al 2007).…”
Section: New Biological Challenges and Opportunitiesmentioning
confidence: 99%